Knowledge and legitimacy in asylum decision-making: the politics of country of origin information. Issue 5 (3rd July 2020) - van der Kist, Jasper; Rosset, Damian
ABSTRACT: State institutions engage in the production of knowledge and representations about the countries of origin of asylum seekers. Building on science and technology studies (STS), critical migration studies and critical citizenship studies, this article analyzes the alignment of government Country of Origin Information (COI) with the public. We examine the different processes through which public legitimacy of asylum knowledge is fostered in three bureaucratic settings. The case studies highlight the variable legitimacy-constructing technologies and practices of publication (Norway), evaluation (United Kingdom) and consultation (European Union) vis-à-vis asylum-relevant information. We demonstrate how this shifting style in the knowledge-based governance of asylum does not consistently enhance legitimacy and stabilization of asylum-relevant information, and can provoke new forms of contestation in this environment of high-stakes policymaking. Finally, we highlight the lack of political subjectivity of asylum seekers to intervene in the production and possibly contest the legitimacy of this information about themselves and their country of origin.